Development and evaluation of an instructional LiveBinders for learning selected computer studies concept in Ilorin Metropolis - Aladesusi, Gboyega Ayodeji; Akindiya, Fatai Oloruntobi (Univeritas Papua, 2021)
This research was developed and evaluated an instructional LiveBinders for learning selected computer Studies concepts in Ilorin Metropolis, Nigeria. In this research, the design and development model was used. The participants in the study were five computer studies teachers, five computer science experts, and five educational technology experts were chosen at random. The following research instruments were used in this study: a developed computer storage device for computer studies, an expert rating guide of educational technology, and a subject content validation questionnaire. Research questions were answered using percentages and mean. The study concluded that if LiveBinders are properly integrated into learning, computer studies learning can be improved. As a result, it was suggested that students be encouraged to use LiveBinders for learning regardless of a subject area.